Pelaksanaan pengajaran dan pembelajaran kemahiran menulis di sekolah rendah - Che Zanariah Che Hassan; Fadzilah Abd Rahman (Penerbit UKM, 2011)
This study focused on the implementation of Malay Language writing skills in the teaching and learning process. The respondents were selected through random sampling among various schools in the Kuala Terengganu district. Writing skills rely on a set of cognitive skills which can be considered very complex. Thus, teachers find it is very hard to apply these skills, where as, the pupils struggle or not even try to develop the skills through out the teaching and learning process in classrooms. For that reasons, a study has been done to determine the profiency level of Malay Language writing skills among the pupils. The finding and tools can be used as guidance for the pupils in improving their writing schools. As for teachers, they could utilize them as alternative in teaching process. The aim of this study is to study the teaching strategies applied by teachers and analyzing the obstacles faced by them as well as the pupils during the Malay Language teaching and learning process. This study has conducted in descriptive way where sets of questionnaires were used with the scale of likert 5. All data collected are processed using the SPSS version 17.0 software and the findings are further explained in quantitative way. Finding showed that the teachers accepted that it was the teachers’ responsibility to teach writing skills, with a highest mean score of 4.61. The report also shows that the teachers accepted the suggestion that content used during the lesson from the range of easy to difficult, with a highest mean score of 4.20. Findings also showed that obstacle occurred in Malay Language teaching and learning process. Among them are lacked of knowledge and teaching skills among teachers and the pupils’ inability in writing skills. This study found that teachers should act positively towards the importance of writing skills and better teaching strategies. Apart from that, teachers should overcome any obstacles occurred during the teaching and learning process creatively. Thus, teacher conducted the lesson in quality way and the pupils have better understanding and improving their writing skills. Teachers should also carry out the lesson based on the latest curriculum